Proceedings of the Twenty-Seventh ACM Symposium on Principles of Distributed Computing 2008
DOI: 10.1145/1400751.1400856
|View full text |Cite
|
Sign up to set email alerts
|

Mobile proactive secret sharing

Abstract: This thesis describes mobile proactive secret sharing (MPSS), an extension of proactive secret sharing. Mobile proactive secret sharing is much more flexible than proactive secret sharing in terms of group membership: instead of the group of shareholders being exactly the same from one epoch to the next, we allow the group to change arbitrarily. In addition, we allow for an increase or decrease of the threshold at each epoch. We give the first known efficient protocol for MPSS in the asynchronous network model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…We also assume the existence of a proactive threshold signature protocol [15], [16], [17], [11], [18] that guarantees that threshold signatures are unforgeable without knowing f or more out of n secret shares.…”
Section: System Model and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also assume the existence of a proactive threshold signature protocol [15], [16], [17], [11], [18] that guarantees that threshold signatures are unforgeable without knowing f or more out of n secret shares.…”
Section: System Model and Assumptionsmentioning
confidence: 99%
“…But no MS replica can know this key, since if it were faulty it could expose it. Therefore, each MS replica holds a share of the associated private key and the signature is produced using a proactive threshold signature scheme [15], [16], [17], [11], [18]. This scheme will only generate a correct signature if f MS þ 1 replicas agree on signing a statement.…”
Section: Reconfiguring the Msmentioning
confidence: 99%
“…Capturing any number of inactive replicas provides no benefit to the attacker. Periodically, or whenever an active replica is in danger, the other active replicas choose at random an inactive replica and run a mobile proactive secret sharing protocol [13] to (1) include the new replica into the active set, and (2) exclude the old replica from the active set. Using pre-established ciphertext replicas, data migration in Evade involves merely transferring small key shares instead of the actual data.…”
Section: E Evade: Avoiding Danger With Lightweight Data Migrationmentioning
confidence: 99%
“…As we discuss in the related work, all known computational VSS scheme [5,37,40] in the asynchronous communication setting rely on homomorphism of commitments. In this section, we show that homomorphism is not necessary for computational VSS in the asynchronous communication setting.…”
Section: Vss In the Asynchronous Communication Modelmentioning
confidence: 99%
“…In the asynchronous communication setting, Cachin et al [5], Zhou et al [40], and more recently Schultz et al [37] suggested computational VSS schemes: AVSS (Asynchronous VSS), APSS (Asynchronous Proactive Secret Sharing), and MPSS (Mobile Proactive Secret Sharing) respectively. Of these, the APSS protocol is impractical for any reasonable n and t, as it has an exponential n t factor in the message complexity (number of messages transferred), while MPSS is developed for a more mobile setting where the set of the system nodes has to change completely between two consecutive phases.…”
Section: Introductionmentioning
confidence: 99%